Soil-Transmitted Helminths Contamination on the Yard's Soil of the Public Elementary Schools in Bandung City - Ratna Dewi Indi Astuti; Ismawati Ismawati; Hilmi Sulaiman Rathomi (Global Medical & Health Communication (GMHC), 2020)
Soil contamination by soil-transmitted helminths (STH) on the schoolyard can act as reservoir STH infection for students. The STH contamination on soil due to contamination of human and animal waste which was disposed of inappropriately. This study aimed to determine the presence of STH eggs in the yard's soil of public elementary schools in Bandung city. This research was an analytic observational study with a cross-sectional approach during September 2019. This study's samples were 97 surface soil of the public elementary schoolyard in Bandung city, selected randomly. Microscopic identification is made for identifying the STH contamination on soil samples. STH contaminates about 66% yard's soil of public elementary schools in Bandung city. We identified larva nematode, Ascaris eggs, Trichuris eggs, Toxocara eggs, and Capillaria eggs. The most common STH we had found was larvae nematode (53%). There is a correlation between flood and human STH contamination on soil (p=0.015). We concluded that STH contaminates the yard's soil of the public elementary schools in Bandung city. The source of STH contamination is from human and animal waste. Flood has a role in spreading human waste on the soil. KONTAMINASI SOIL-TRANSMITTED HELMINTH PADA TANAH PEKARANGAN SEKOLAH DASAR NEGERI KOTA BANDUNGPencemaran tanah oleh soil-transmitted helminth (STH) di halaman sekolah dapat menjadi reservoir penularan STH bagi siswa. Pencemaran ini dapat terjadi akibat pengelolaan kotoran manusia dan hewan yang tidak tepat. Penelitian ini bertujuan mengetahui keberadaan telur STH di tanah pekarangan sekolah dasar negeri di Kota Bandung. Penelitian ini merupakan penelitian observasional analitik dengan pendekatan cross-sectional yang dilaksanakan pada bulan September 2019. Sampel penelitian berjumlah 97 tanah permukaan halaman sekolah dasar negeri di Kota Bandung yang dipilih secara acak. Identifikasi mikroskopis dilakukan untuk mengidentifikasi kontaminasi STH pada sampel tanah. Data banjir didapatkan dari wawancara dengan penduduk sekitar. Pencemaran STH terjadi pada 66% sampel. Kami mengidentifikasi larva nematoda, telur Ascaris, telur Trichuris, telur Toxocara, dan telur Capillaria. Jenis STH yang paling banyak ditemukan adalah larva nematoda (53%). Terdapat korelasi antara banjir dan pencemaran STH manusia di tanah (p=0,015). Kami menyimpulkan bahwa tanah pekarangan sekolah dasar negeri di Kota Bandung tercemar STH. Sumber pencemaran STH berasal dari kotoran manusia dan hewan. Banjir berperan dalam menyebarkan kotoran manusia di tanah.